Appraising the causal association between Crohn’s disease and breast cancer: a Mendelian randomization study - Yu, Chengdong; Xu, Jiawei; Xu, Siyi; Huang, Yanxiao; Tang, Lei; Zeng, Xiaoqiang; Yu, Tenghua; Chen, Wen; Sun, Zhengkui (Frontiers in Oncology, 2024)
Background: Previous research has indicated that there may be a link between Crohn's disease (CD) and breast cancer (BC), but the causality remains unclear. This study aimed to investigate the causal association between CD and BC using Mendelian randomization (MR) analysis.The summary data for CD (5,956 cases/14,927 controls) was obtained from the International Inflammatory Bowel Disease Genetics Consortium (IIBDGC). And the summary data for BC (122,977 cases/105,974 controls) was extracted from the Breast Cancer Association Consortium (BCAC). Based on the estrogen receptor status, the cases were classified into two subtypes: estrogen receptor-positive (ER + ) BC and estrogen receptor-negative (ER -) BC. We used the inverse variance weighted method as the primary approach for two-sample MR. MR-PRESSO method was used to rule out outliers. Heterogeneity and pleiotropy tests were carried out to improve the accuracy of results.Additionally, multivariable MR was conducted by adjusting for possible confounders to ensure the stability of the results.The two-sample MR indicated that CD increased the risks of overall (OR: 1.020; 95% CI: 1.010-1.031; p=0.000106), ER + (OR: 1.019; 95%CI: 1.006-1.034; p=0.006) and ER -BC (OR: 1.019; 95%CI: 1.000-1.037; p=0.046) after removal of outliers by MR-PRESSO. This result was reliable in the sensitivity analysis, including Cochran's Q and MR-Egger regression. In multivariate MR analyses, after adjusting for smoking and drinking separately or concurrently, the positive association between CD and the risks of overall and ER + BC remained, but it disappeared in ER -BC. Furthermore, reverse MR analysis suggested that BC did not have a significant impact on CD risk.Our findings provide evidence for a possible positive association between CD and the risk of BC. However, further studies are needed to fully understand the underlying mechanisms and establish a stronger causal relationship.